Predicting adult obesity from childhood obesity: a systematic review and meta‐analysis. (23rd December 2015) - Simmonds, M.; Llewellyn, A.; Owen, C. G.; Woolacott, N.
Summary: A systematic review and meta‐analysis was performed to investigate the ability of simple measures of childhood obesity such as body mass index (BMI) to predict future obesity in adolescence and adulthood. Large cohort studies, which measured obesity both in childhood and in later adolescence or adulthood, using any recognized measure of obesity were sought. Study quality was assessed. Studies were pooled using diagnostic meta‐analysis methods. Fifteen prospective cohort studies were included in the meta‐analysis. BMI was the only measure of obesity reported in any study, with 200, 777 participants followed up. Obese children and adolescents were around five times more likely to be obese in adulthood than those who were not obese. Around 55% of obese children go on to be obese in adolescence, around 80% of obese adolescents will still be obese in adulthood and around 70% will be obese over age 30. Therefore, action to reduce and prevent obesity in these adolescents is needed. However, 70% of obese adults were not obese in childhood or adolescence, so targeting obesity reduction solely at obese or overweight children needs to be considered carefully as this may not substantially reduce the overall burden of adult obesity.